2016
DOI: 10.1051/0004-6361/201628700
|View full text |Cite
|
Sign up to set email alerts
|

A machine learned classifier for RR Lyrae in the VVV survey

Abstract: Variable stars of RR Lyrae type are a prime tool with which to obtain distances to old stellar populations in the Milky Way. One of the main aims of the Vista Variables in the Via Lactea (VVV) near-infrared survey is to use them to map the structure of the Galactic Bulge. Owing to the large number of expected sources, this requires an automated mechanism for selecting RR Lyrae, and particularly those of the more easily recognized type ab (i.e., fundamental-mode pulsators), from the 10 6 −10 7 variables expecte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 29 publications
2
60
0
Order By: Relevance
“…The quoted circumstantial evidence indicates that we still lack a homogenous and detailed analysis of the Bailey diagram as a function of the metal content. In this context it is worth mentioning that we are neglecting the metallicity estimates based either on photometric indices such as the inversion of the PL relation (Braga et al 2016;Martínez-Vázquez et al 2016;Bono et al 2019) or the Fourier decomposition of the light curve (Jurcsik & Kovacs 1996;Nemec et al 2013;Elorrieta et al 2016;Hajdu et al 2018). Data plotted in Fig.…”
Section: The Fine Structure Of the Bailey Diagrammentioning
confidence: 99%
“…The quoted circumstantial evidence indicates that we still lack a homogenous and detailed analysis of the Bailey diagram as a function of the metal content. In this context it is worth mentioning that we are neglecting the metallicity estimates based either on photometric indices such as the inversion of the PL relation (Braga et al 2016;Martínez-Vázquez et al 2016;Bono et al 2019) or the Fourier decomposition of the light curve (Jurcsik & Kovacs 1996;Nemec et al 2013;Elorrieta et al 2016;Hajdu et al 2018). Data plotted in Fig.…”
Section: The Fine Structure Of the Bailey Diagrammentioning
confidence: 99%
“…For example, Dubath et al (2011) applied Random Forest classification to Hipparcos data, while Richards et al (2012) applied the same general technique to techniques to automatically classify variable stars from the ASAS survey. In contrast, Palaversa et al (2013) used support vector machine (Cortes & Vapnik 1995) based machine learning to classify periodic variables from the LINEAR survey, and Elorrieta et al (2016) have found that the AdaBoost technique (Freund & Schapire 1997) provides encouraging results in the case of the NIR light curves obtained by the Vista Variables in the Vía Láctea survey (Minniti et al 2010).…”
Section: Automated Pre-classificationmentioning
confidence: 99%
“…The same year Richards et al (2011) obtained the same conclusions using 53 features. Recent works still apply the same techniques to find specific classes of variability (Elorrieta et al 2016;Gran et al 2016). Pichara et al (2012), working with the EROS database (Beaulieu et al 1995), included autoregressive features which prove valuable for QSO classification.…”
Section: Introductionmentioning
confidence: 99%